2019
DOI: 10.1021/acs.oprd.9b00255
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Halide Inhibition of Suzuki–Miyaura Couplings with Biaryl Monophosphine-Based Catalysts

Abstract: The Suzuki−Miyaura reaction is one of the most widely employed transformations in synthetic chemistry. Despite extensive investigation, questions remain about the mechanistic nature of the transmetalation step when catalysts based on advanced ligands such as biaryl monophosphines are used, impeding the development of improved catalysts. Here we demonstrate that the often overlooked halide salt (KX) generated as a byproduct of cross-coupling renders the transmetalation step reversible with SPhos-based catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Both 5‐chloro‐2‐iodoaniline and 2‐bromo‐5‐chloroaniline could be successfully employed as starting materials for the synthesis of biphenyl 1j (Scheme ). Interestingly, the bromoaniline was found to be more reactive than the iodoaniline, which may be attributed to the inhibiting effect of KI (generated during the reaction), on Suzuki–Miyaura reactions in aqueous THF as previously reported by Milner and co‐workers . Whereas 2‐bromo‐5‐chloroaniline reacted to give 1j with full consumption of the starting material, a significant amount of starting material could be recovered when 5‐chloro‐2‐iodoaniline was used, supporting the potential inhibiting effect of in situ generated KI.…”
Section: Resultssupporting
confidence: 76%
“…Both 5‐chloro‐2‐iodoaniline and 2‐bromo‐5‐chloroaniline could be successfully employed as starting materials for the synthesis of biphenyl 1j (Scheme ). Interestingly, the bromoaniline was found to be more reactive than the iodoaniline, which may be attributed to the inhibiting effect of KI (generated during the reaction), on Suzuki–Miyaura reactions in aqueous THF as previously reported by Milner and co‐workers . Whereas 2‐bromo‐5‐chloroaniline reacted to give 1j with full consumption of the starting material, a significant amount of starting material could be recovered when 5‐chloro‐2‐iodoaniline was used, supporting the potential inhibiting effect of in situ generated KI.…”
Section: Resultssupporting
confidence: 76%
“…By changing the solvent in the biphasic reaction system from THF to toluene, this inhibition was effectively minimized. The study also revealed that inhibition by halide is likely a more general problem in metal-catalyzed cross-coupling reactions, in particular the ones that involve a reversible transmetalation step …”
Section: Synthesis and Applications Of L1pd(0) Precatalystsmentioning
confidence: 96%
“…4. [40][41][42] Firstly, aer the addition of aryl halides, the Pd complex (Ar-Pd-X) was formed over C-Pd catalyst via oxidative addition. The complex then formed an Ar-Pd-Ph complex with phenylboronic acid in the presence of K 2 CO 3 .…”
Section: Catalytic Activity Of the C-pd Catalystmentioning
confidence: 99%